Longitudinal assessment of swimming performance in the 200-m freestyle event - Costa, M. J.; Bragada, J. A.; Marinho, D. A.; Reis, V. M.; Silva, A. J.; Barbosa, T. M. (The Open Sports Sciences Journal, 2010)
The aim of this study was to track and analyze the 200-m Freestyle performance stability throughout elite swimmer`s career. 29 Portuguese male top-50 were analyzed for seven consecutive seasons between 12 and 18 years old. Best performances were collected from ranking tables. Longitudinal assessment was performed based on two approaches: (i) mean stability was analyzed by descriptive statistics and ANOVA repeated measures for each season followed by a post-hoc test (Bonferroni test), (ii) normative stability was analyzed with self-correlation (Malina, 2001) and the Cohen`s Kappa tracking index (Landis and Koch, 1977). There was a 200-m Freestyle performance enhancement from children to adult age. The overall career performance prediction was moderate. The change from 13 to 14 years can be a milestone, where the ability to predict the final swimmer`s performance level strongly increases